Alternative Temporalities: Ways of Imagining the Passing of Time - Herrero, Montserrat (REVISTA DE HISTORIOGRAFÍA (RevHisto), 2020)
Recent articles published in the last decade on theoretical aspects related to history deal with re-imagining the relationship between the past and the present in history. This article calls “alternative temporalities” those temporalities that imagine time and its passing in an anti-lineal way, cyclical and attuned to the persistence of the past in the unfolding of the present and future, and vice-versa. Koselleck’s theory of history has done much for these ways of representing historical temporality. In particular, his notion of “horizon of expectation” opens the way to the prominence of the future in the representations of historical time. The article delves into Koselleck’s reflections on the theological-political derivation of the idea of the future rooted in eschatological prophecy, to follow the thread of this idea and lead it beyond the conclusions of Koselleck, following the point of view of some philosophers of 20th Century.